Association between bilirubin levels with incidence and prognosis of stroke: A meta-analysis - Zhao, Kun; Wang, Rui; Chen, Rongrong; Liu, Jialei; Ye, Qing; Wang, Kai; Li, Juebao (Frontiers in Neuroscience, 2023)
Objective: Bilirubin has anti-inflammatory, antioxidant, and neuroprotective properties, but the association between bilirubin and stroke remains contentious. A meta-analysis of extensive observational studies on the relationship was conducted. Methods: Studies published before August 2022 were searched in PubMed, EMBASE, and Cochrane Library. Cohort, cross-sectional and case-control studies that examined the association between circulating bilirubin and stroke were included. The primary outcome included the incidence of stroke and bilirubin quantitative expression level between stroke and control, and the secondary outcome was stroke severity. All pooled outcome measures were determined using random-effects models. The meta-analysis, subgroup analysis, and sensitivity analysis were performed using Stata 17. Results：A total of seventeen studies were included. Patients with stroke had a lower total bilirubin level (mean difference = -1.33 μmol/L, 95%CI: -2.12 – -0.53, P < 0.001). Compared with the lowest bilirubin level, total odds ratio (OR) of the highest bilirubin for the occurrence of stroke was 0.71(95% CI: 0.61 – 0.82) and ischemic stroke was 0.72(95% CI: 0.57, 0.91), especially in cohort studies with accepted heterogeneity (I2 = 0). Serum total and direct bilirubin levels were significantly and positively associated with stroke severity. A stratified analysis based on gender showed that the total bilirubin level in males correlated with ischemic stroke or stroke, which was not noted in females. Conclusion: While our findings suggest associations between bilirubin levels and stroke risk, existing evidence is insufficient to establish a definitive association. Better-designed prospective cohort studies should further clarify pertinent questions. (PROSPERO registration number: CRD42022374893)